Will urbanization raise social mobility in the South, replicating the economic history of the West? - Emily Rains; Anirudh Krishna (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
As developing countries rapidly urbanize, the number of people living in 'slums'-neighbourhoods lacking property rights and basic services-continues to increase. Whether slum residents will ultimately share in the benefits of the cities they help build or will remain trapped in poverty is not well understood. We review empirical evidence on the potential for social mobility in today's urban slums in order to assess prospects for upward mobility in cities of the Global South. Finding evidence for limited levels of upward mobility and high levels of volatility, we discuss the substantial public sector interventions that accompanied urbanization in the Global North. We argue that urbanization will not automatically improve prospects for mobility for the urban poor. Instead, it will be critical to implement appropriately nuanced interventions to improve opportunities for the billions residing in today's and tomorrow's slums.
Keywords: 330; Entwicklungsländer; Developing countries; Beispielhafte Fälle; Exemplary cases